Combinational effects of Ni precursors on Ni/YSZ cermet anode - Han, Kyoung R.; Jung, Yoonji; Kim, Chang-Sam; Lee, Haiwon (TRANS TECH PUBLICATIONS LTD, 2006)
NiO/YSZ composite powder with 70 wt% of NiO was prepared by surface modification of similar to 30 nm YSZ with Ni precursors. As Ni precursors, acidic nickel nitrate and basic nickel carbonate were employed. By varying the ratio of Ni precursors, substantially different particle sizes were obtained. Their Ni/YSZ cermets also showed substantially different microstructures and porosities. Effects of combination of Ni precursors on Ni/YSZ cermets were studied by using XRD, zetapotential, and SEM.
Keywords: POWDER